2009
DOI: 10.1021/ja907409z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Charge Transfer through DNA by Replacing Adenine with Diaminopurine

Abstract: A positive charge migrates along DNA mainly via a series of short-range charge transfer (CT) processes between G-C base pairs, which have relatively high HOMO levels. As such, the CT efficiency sharply decreases with the insertion of A-T base pairs between the G-C base pairs. We have previously demonstrated that the CT efficiency through DNA can be dramatically increased by using deazaadenine (Z), an analogue of A, to adjust the HOMO levels of the A-T base pairs closer to those of the G-C base pairs (Nat. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…72,73 In a more extensive study, a good correlation was observed between the rate of formation of PTZ •+ in NI–PTZ systems and Δ HOMO between the low potential sites G, D, and 8-bromoguanine, and the high potential sites 2-aminopurine (Ap), A, 8-bromoadenine, and thymine when low and high potential sites were placed in alternating sequences. 74 In this study, it was the difference in HOMO energies, rather than the absolute HOMO energies, that affected the rate of CT.…”
Section: Dna Ct In Solutionmentioning
confidence: 97%
“…72,73 In a more extensive study, a good correlation was observed between the rate of formation of PTZ •+ in NI–PTZ systems and Δ HOMO between the low potential sites G, D, and 8-bromoguanine, and the high potential sites 2-aminopurine (Ap), A, 8-bromoadenine, and thymine when low and high potential sites were placed in alternating sequences. 74 In this study, it was the difference in HOMO energies, rather than the absolute HOMO energies, that affected the rate of CT.…”
Section: Dna Ct In Solutionmentioning
confidence: 97%
“…Recent experiments have demonstrated that the rates of CT processes in DNA hairpins depend not only on the distance between the donor and the acceptor sites but on the base pair sequence (32)(33)(34)(35)(36)(37). In particular, it has been found that sequences containing both guanine:cytosine (G:C) and adenine:thymine (A:T) base pairs exhibit a faster hole transfer between S a and S b than sequences involving only A:T base pairs (32,33).…”
mentioning
confidence: 99%
“…Recent ultrafast nonlinear optical spectroscopy has revealed the temporal behavior of relaxation process of the photoexcited molecular chain [7,8]. Also in biomolecules, such as α-helix protein and DNA strands, which consist of molecular chain structures, the transport process in a nonequilibrium state have been extensively studied in order to clarify the biofunctions of these molecules from a microscopic viewpoint [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%